2007
DOI: 10.4049/jimmunol.179.1.247
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Activation during Influenza Virus Infection Unveils a Novel Pathway of IFN-γ Production by Phagocytic Cells

Abstract: The contribution of environmental factors is important as we consider reasons that underlie differential susceptibility to influenza virus. Aryl hydrocarbon receptor (AhR) activation by the pollutant dioxin during influenza virus infection decreases survival, which correlates with a 4-fold increase in pulmonary IFN-γ levels. We report here that the majority of IFN-γ-producing cells in the lung are neutrophils and macrophages not lymphocytes, and elevated IFN-γ is associated with increased pulmonary inducible N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 61 publications
4
64
0
Order By: Relevance
“…Leukocytes from the airways were collected by bronchoalveolar lavage (BAL) with cold RPMI 1640 containing 1% BSA as previously described (41). Leukocytes from the entire lung were obtained by digesting intact (i.e., not subjected to lavage) lungs with collagenase (RPMI 1640 medium containing 0.7 mg/ml collagenase A [Worthington Biochemical Corp.], 30 g/ml DNase I, 2.5% fetal bovine serum [FBS], and 10 mM HEPES) (29). Prior to instillation of the collagenase solution via the trachea, circulating leukocytes were removed from the pulmonary vasculature by perfusing 5 ml of PBS containing 2 mM EDTA via the right ventricle.…”
Section: Methodsmentioning
confidence: 99%
“…Leukocytes from the airways were collected by bronchoalveolar lavage (BAL) with cold RPMI 1640 containing 1% BSA as previously described (41). Leukocytes from the entire lung were obtained by digesting intact (i.e., not subjected to lavage) lungs with collagenase (RPMI 1640 medium containing 0.7 mg/ml collagenase A [Worthington Biochemical Corp.], 30 g/ml DNase I, 2.5% fetal bovine serum [FBS], and 10 mM HEPES) (29). Prior to instillation of the collagenase solution via the trachea, circulating leukocytes were removed from the pulmonary vasculature by perfusing 5 ml of PBS containing 2 mM EDTA via the right ventricle.…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been shown that lungs of IAV-infected mice are infiltrated by neutrophils expressing CD11b and Gr-1 markers (39,40). Since it is known that alteration of cytokines during acute and chronic inflammations results in the expansion of ARG-1- and NOS-expressing MDSCs (i.e., CD11b + Gr-1 + cells) (10) and since cytokines and chemokines are elevated during influenza virus infection (3, 41), we measured the frequency and activity of MDSCs in the lungs of PR8-infected WT, Jα18 -/-, and CD1d -/-mice ( Figure 2A).…”
Section: Inkt Cell-dependent Resistance To Lethal Intranasal Injectiomentioning
confidence: 99%
“…Darkness could be determined by minimum intensity and cragginess could be measured as a frequent change in the intensity of brightfield signal within the cells (Gradient RMS). ImageStream analysis of cell and nuclear shape combined with immunophenotype has been used by other investigators to define cells produced during ES cell differentiation, cells bound by natural killer cells, and which cells are producing IFN-gamma (Kim et al, 2007;Neff-LaFord et al, 2007;Woll et al, 2008). There are a growing number of investigators using the ImageStream to quantify colocalization of proteins or the extent of a protein's localization within the nucleus (Beum et al, 2006;Liu et al, 2007;Matsuda et al, 2007;Ramos et al, 2007).…”
mentioning
confidence: 99%